The European Green Deal and the energy transition: challenges and opportunities for industrial companies - Jorge Fernández Gómez (Boletín de Estudios Económicos)
This article reviews the challenges and opportunities facing industrial companies in europe as a result of the implementation of the European Green Deal, the growth and competitiveness strategy for the European Union announced by the European Commission in December 2019. The objective of achieving a reduction of 55% in greenhouse gas (GHG) emissions in 2030 relative to 1990 and zero net emissions in 2050 will force industrial companies to take urgent steps to decarbonize their activities. This will imply profound changes in their business operations and the need to invest in new technologies and processes and substitute clean energy for conventional fossil fuels. In order to support this transformation, sound innovation policies must be put in place and an efficient sustainable finance ecosystem must be developed. The article explores how industrial companies can transform their operations while simultaneously complying with the grand objectives of the European Green Deal and preserving and even enhancing their competitiveness.